What makes education Catholic : spiritual foundations - Groome, Thomas H. (New York: Orbis books, 2021)
"Offers the spiritual foundations that should define/suffuse Catholic education, at every level, to ensure that Catholic schools are providing the education that they promise"--
Includes bibliographical references and index.
Keywords: Catholic Church -- Education -- Philosophy; Catholic Church -- Doctrines -- Education; Catholic schools; Education (Christian theology)